Moses the Egyptian : the memory of Egypt in western monotheism - Assmann, Jan (Harvard University Press, 1997)
Moses is at the foundation of monotheism, and so of Western culture. Here the factual and fictional events and characters in religious beliefs are studied. It traces monotheism back to the Egyptian king Akhenaten and shows how Moses's followers established truth by denouncing all others as false.